Improved in vitro and in vivo Anti-Candida albicans Activity of Cymbopogon nardus Essential Oil by Its Incorporation into a Microemulsion System - Gaspar de Toledo L; dos Santos Ramos MA; Bento da Silva P; Rodero CF; de Sá Gomes V; Noronha da Silva A; Pavan FR; da Silva IC; Bombarda Oda F; Flumignan DL; Gonzaga dos Santos A; Chorilli M; et al. (International Journal of Nanomedicine, 2020)
Luciani Gaspar de Toledo,1 Matheus Aparecido dos Santos Ramos,1 Patrícia Bento da Silva,2 Camila Fernanda Rodero,3 Veridiana de Sá Gomes,1 Anderson Noronha da Silva,1 Fernando Rogério Pavan,1 Isabel Cristiane da Silva,1 Fernando Bombarda Oda,4 Danilo Luis Flumignan,5 André Gonzaga dos Santos,4 Marlus Chorilli,3 Margarete Teresa Gottardo de Almeida,6 Taís Maria Bauab1 1School of Pharmaceutical Sciences, Department of Biological Sciences, São Paulo State University (UNESP), São Paulo, Brazil; 2Department of Genetics and Morphology, University of Brasília (UnB), Institute of Biological Sciences, Brasília, Distrito Federal, Brazil; 3School of Pharmaceutical Sciences, Department of Drug and Medicines, São Paulo State University (UNESP), São Paulo, Brazil; 4School of Pharmaceutical Sciences, Department of Natural Active Principles and Toxicology, São Paulo State University (UNESP), São Paulo, Brazil; 5São Paulo Federal Institute of Education, Science and Technology (IFSP), São Paulo, Brazil; 6Faculty of Medicine of São José do Rio Preto (FAMERP), Department of Infectious Diseases, São José do Rio Preto, São Paulo, BrazilCorrespondence: Taís Maria BauabSchool of Pharmaceutical Sciences, Department of Biological Sciences, São Paulo State University (UNESP), Campus Araraquara, São Paulo 14800-903, BrazilTel +55-16-3301-6955Fax +55-16-3322-0073Email tais.bauab@unesp.brPurpose: Vulvovaginal candidiasis (VVC) is an opportunistic fungal infection that adversely affects a woman’s health, due to unpleasant symptoms, therapeutic challenges, and the emergence of resistant strains. The association of natural products and nanotechnology is important to improve the antifungal potential of medicinal plants. We aimed to evaluate the in vitro and in vivo anti-Candida albicans activity of unloaded (EO) and loaded (ME+EO) essential oil of Cymbopogon nardus in the microemulsion (ME).Methods: The chemical analysis of the EO was performed by gas chromatography-mass spectrometry. The ME and ME+EO were characterized by scattering, zeta potential, polarized light microscopy, rheological assays, mucoadhesiveness and transmission electronic microscopy. The in vitro antifungal activity of the EO and ME+EO were evaluated by microdilution technique. The toxicity of EO and ME+EO was analyzed on human cell line HaCat and using alternative model assay with Artemia salina. The experimental in vivo VVC was performed in female mice (C57BL/6).Results: The main compounds of the EO were found to be citronellal, geranial, geraniol, citronellol, and neral. The formulations exhibited suitable size, homogeneity, negative charge, isotropic behavior, highly organized structure, and pseudoplastic behavior, for vaginal application. TEM photomicrographs showed possible EO droplets inside the spherical structures. The EO, when loaded into the ME, exhibited an improvement in its antifungal action against C. albicans. The EO was not toxic against brine shrimp nauplii. An in vivo VVC assay showed that the use of the ME significantly improved the action of the EO, since only the ME+EO promoted the eradication of the fungal vaginal infection on the third day of treatment.Conclusion: The EO and ME+EO are promising alternatives for the control of fungal infections caused by C. albicans, once the use of nanotechnology significantly improved the antifungal action of the EO, especially in an in vivo model of VVC.Keywords: nanostructured lipid system, citronella, vulvovaginal candidiasis, therapeutic treatment